MEKANISME DAN CARA PENYELESAIAN PEMBIAYAAN BERMASALAH - Azhari, Fathurrahman (Islamic Economics and Business Faculty of UIN Antasari, 2012)
Islamic Financial Units (IFU), both banks and non-banks, have main activities to col-lect funds from people (clients) and then distribute them through financing, loan and services.After the units as investors distribute the funds to business managers, there are two possibilities:the business runs well because of good management or bad management leads to an unability onthe side of the managers to pay regular installments. In a situation when a dispute occurs betweenparties involved in a financing contract, maybe in the case of non-performing loan due to badbusiness management, or because one party does not fulfill the obligation, or some imperfectionsin the financing contract lead to different ways of understanding it, the resolution mechanismsare available in either court of law or outside it. This article discusses the legal bases for disputeresolutions through both ways, which include some laws, the regulations of the Indonesian Cen-tral Bank, an Islamic banks dispute resolution procedure, and the legal opinion of Sharia Na-tional Council.